The effect of platelet-rich fibrin (PRF) versus freeze-dried bone allograft (FDBA) used in alveolar ridge preservation on the peri-implant soft and hard tissues: a randomized clinical trial - Hassan Azangookhiavi; Sareh Habibzadeh; Houyar Zahmatkesh; Ehsan Mellati; Seyed Ali Mosaddad; Yalda Dadpour (BMC, 2024)
Abstract Background The effectiveness of alveolar ridge preservation on bone regeneration and tissue healing has been thoroughly documented in the literature. This study aimed to evaluate the peri-implant soft and hard tissue changes after alveolar ridge preservation using either platelet-rich fibrin (PRF) or freeze-dried bone allograft (FDBA) over a 12-month period following the prosthetic loading of implants. Methods In this randomized clinical trial, 40 individuals were recruited for alveolar ridge preservation using (1) FDBA or (2) PRF in incisal/premolar areas. At two follow-up sessions (six- and 12-months post-implant insertion), radiographic imaging and clinical examinations assessed marginal bone loss and soft tissue factors, including gingival recession and bleeding on probing. The differences between study groups were analyzed using Generalized estimating Equations, the Binary logistic regression model, and Cochran's Q test. Results There was a statistically significant difference regarding gingival recession at both follow-up evaluations; values in the PRF group were considerably lower compared to the FDBA group (p < 0.05). The mean values for vertical marginal bone loss and bleeding on probing showed no significant differences between the two study groups (p > 0.05). Conclusions Except for gingival recession, applying PRF yielded comparable clinical results to FDBA after one year of implant loading and could be recommended as a potential biomaterial for alveolar ridge preservation following tooth extractions. Clinical trial registration The research protocol was registered in the Protocol Registration and Results System on 13/08/2021, available at https://clinicaltrials.gov/ (NCT05005377).